Tema: Análisis del artefacto vestimentario del diablo en la fiesta popular: caso de estudio el diablo de hojalata de Riobamba - Bautista Sánchez, Daniela Estefanía (2024)
The aim of this research project is to analyze the attire of the Tin Devil in the city of Riobamba, with the purpose of contributing to the collective memory. The Tin Devil is a central figure in the popular festivity of the "Pase del niño Rey de Reyes" in Riobamba, Ecuador. This festivity holds great cultural value in the city. The Tin Devil was declared intangible cultural heritage in January 2017. This study seeks to identify the cultural value of this festivity, while also conducting an analysis of its origin, history, and its influence on the characterization of the character through a literature review and consideration of the criteria of the Riobamba population. Furthermore, the morphological and symbolic aspects of the character will be contrasted through the use of tools such as diagnostic observations of the attire of the Tin Devil, taking into account that the character possesses elements that are not part of the costume but representative accessories, with the aim of obtaining a clear and concise understanding. Finally, a written report will be developed consolidating the significant characteristics of the Tin Devil's attire, emphasizing all the information analyzed in the research. In summary, this study aims to analyze the attire of the Tin Devil in the city of Riobamba to contribute to the collective memory and understand its cultural value in the festivity of the "Pase del niño rey de reyes".